Prevention of Iatrogenic Keratectasia - Rapuano, C. J. (Klinische Monatsblätter für Augenheilkunde, 2016)
Iatrogenic corneal ectasia is a rare but devastating complication after refractive surgery. While its incidence appears to be declining, it has not been eliminated. Its cause is probably related to a combination of an intrinsic predisposition to ectasia and an additional anatomical destabilising effect from the refractive surgery. Determining which eyes are intrinsically “weak” and exactly how much additional “weakening” an eye can withstand before developing progressive thinning and protrusion are both difficult tasks. The essentially universal availability of corneal topography and the increasing use of corneal tomography have significantly improved our ability to preoperatively diagnose early forms of corneal ectasias, especially keratoconus and pellucid marginal degeneration. Advanced software algorithms have also enhanced the sensitivity and specificity of these technologies. Newer technologies, such as measuring corneal biomechanics and corneal epithelial distribution, will hopefully continue to help us to differentiate normal from abnormal corneas preoperatively. In addition to abnormalities in anterior and posterior corneal curvature, a number of other risk factors for the development of post-refractive surgery ectasia have been proposed, including younger patient age, thinner central corneal thickness, thinner residual stromal bed thickness and high myopia. If the percentage of altered tissue is > 40 %, this is an extremely accurate predictor of corneal ectasia after refractive surgery. While there are a number of effective treatments for iatrogenic corneal ectasia, such as contact lenses, corneal crosslinking, intracorneal rings and corneal transplantation, prevention should be the goal. With newer and better corneal imaging technology to help screen out patients with abnormal corneas along with an improved understanding of exactly how much weakening a given cornea can take, we should be able to minimize this vision threatening complication.
Keywords: cornea; refractive surgery; genetics